(untitled) (Journal of Rangpur Medical College, 2024)
Background: Bicipital groove is a shallow sulcus at its head-shaft junction of the humerus which has significance in post-mortem anthropology, archaeology and in clinical practice for orthopaedic surgeons. Objective: To determine length, width and depth of bicipital groove of adult human dry humerus. Methods: This cross-sectional study was conducted in the Department of Anatomy, Rangpur Medical College between the periods of July 2020 to June 2021. Two hundred dry adult humerus bones were collected purposively from 1st and 2nd year MBBS and BDS students of Department of Anatomy, Rangpur Medical College, Rangpur. Among the 200 humerus, 106 were right and 94 were left sided humerus including 41 paired bone. The length, width and depth of bicipital groove were measured. From the measurements mean and standard deviation was calculated for each variable.The student’s‘t’ testwas done for comparison of these variables and correlation test was done to find out the correlation with the total length of humerus withbicipital groove length (BGL)by using SPSS version 16. Results: In the present study, it was observed that the values of the length of bicipital groove was higher in the left side but the value of width of the groove was significantly higher on the right side of the total humerus but in paired bones, all the variables were higher in right side. Significant positive correlation found between the length of BG to total length of humerus. Conclusions: In the present study width of BG was significantly higher on the right side indicating robustness of right biceps brachii and thus right handedness. The positive correlation of BG with total length of humerus would help in determination of length of humerus in forensic investigation. J Rang Med Col. September 2024; Vol. 9, No. 2: 84-88